Revisiting the paleomires of western India: An insight into the early Paleogene lignite Corridor. (March 2019) - Singh, Vijay K.; Rajak, Pramod K.; Singh, Prakash K.
Graphical abstract: Highlights: During the Paleocene-Eocene period the peat forming basins of western India were located closer to the equator. The black bands of lignites are strongly gelified compared to the brownish bands and the study reveals that there is dominance of huminite followed by liptinite and inertinite maceral groups. A high GI and low TPI values suggest a continuous wet condition in the basin and the GWI and VI values are also suggestive of mesotrophic to rheotrophic condition. The paleomires evolved during the transgressive phase under coastal marshy setting but there were intermittent episodes of fluvial activities. Abstract: The Paleocene-Eocene lignite sequences of Western India occur in the Bikaner-Nagaur (Barsingsar, Gurha and Kasnau-Matasukh lignite seams) and Barmer (Kapurdi and Giral lignite seams) basins of Rajasthan, whereas those in the Cambay (Vastan, Rajpardi and Tadkeshwar lignite seams), Saurashtra (Bhavnagar upper and lower lignite seams), and Kachchh (Matanomadh and Panandhro lignite seams) basins are located in Gujarat. The position of the Cambay basin (Gujarat), being closer to the equator during the Early Eocene period, makes it pertinent to understand the variations in petrographic and geochemical constituents of Gujarat and Rajasthan lignites in space and time. Floral growth, which largely depends on the climate of the region and its geographical location, has an important role in the formation of mire. Nevertheless, the peat forming plant communities, nutrient supply, bacterial activity, types of deposition, temperature, pH and redox potential impart various characteristics to coal and are reflected in macerals. Black bands, in Gujarat and Rajasthan lignites, are strongly gelified compared to brownish bands and are stratified in nature. They are dominantly composed of huminite maceral group, while liptinites and inertinites occur in subordinated amount. These lignites of Gujarat and Rajasthan have high values of gelification index (GI) and low tissue preservation index (TPI), indicating thereby a continuous presence of wet condition in the basin and slow subsidence rate. However, due to fluctuating water level in the basins, few sections experienced relatively oxic episodes indicated by relatively high inertinite content. Study of the ground water index (GWI) and vegetation index (VI) of these lignites indicates rheotrophic to mesotrophic hydrological condition. The study revealed that the lignites of Rajasthan and Gujarat were formed during the transgressive phase under coastal marshy setting. However, there were intermittent episodes of fluvial activities which gave rise to supratidal flood plains.